Analysis of Noise Measurement at Engine Room Station: A Case Study on PT Socfindo Seunagan - Irvan Mahendra; Nissa Prasanti (Jurnal Inotera, 2023)
Noise is one of the factors that can interfere with the welfare and comfort of employees' work. Too high noise can cause hearing loss, stress, and decreased concentration. Therefore, it is important to measure the noise level in the work environment and take the necessary measures to reduce the unsafe noise level. To measure the noise level at the machine room station PT. Socfindo Seunagan, the researcher used a noise measuring instrument that corresponds to the dar booth (sound Level Meter). This research was conducted at several points at the PT machine room station. Socfindo Seunagan, including near the main machines, around the production area, and in the employee's work area. The results showed that the noise level in the machine room station PT. Socfindo Seunagan exceeds the safe limits set by the Indonesian National standard. The highest noise level detected was 174 dB(A). Based on the results of this study, measures are needed to reduce the noise level at the PT. Socfindo Seunagan in order not to harm the welfare and comfort of work of employees. Possible actions include the use of ear protection, reduction of noise sources, and rearrangement of the layout of the engine room station.